(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The features of light refraction in the anterior segment of the eye and after dispersion on the posterior surface of the cornea are considered. It is shown that the cornea refracts the light as a weakly scattering lens. The conclusion is made that the optical system of the eye is essentially a kind of natural telescope. The main task of the anterior segment of the eye is the optical compression of the light coming from the surrounding into a beam (tunnel) of light 1.8–2.5 mm in diameter, which can pass to the foveola even through a narrow pupil. The concept of «a light tunnel» was introduced. The task of the eye lens is the effective optical control of the three basic dispersion bands of blue, green and red colors (RGB-bands) in «the light tunnel». The optical control is carried out with the two mini-lenses located in the center of the anterior and posterior surfaces of the lens capsule. Perhaps, the main mechanism of lens accommodation is the changes in the curvature of these mini-lenses when looking closer or farther away. The executive mechanism of «tunneling» accommodation is the varying pressure inside the lens, which is maximal when viewed near, when the elastic capsule of the lens is slightly stretched, and it can most strongly compress the lens masses. Taking into account the physiological makers of the ways of delivery and removal of aqueous humor, which is necessary to maintain the metabolism of the internal structures of the lens, a practical conclusion is made about the possible rate of cataract development in hypermetropic and myopic patients when optical correction is prescribed improperly. Recommendations for rational optical correction are given.